2012
DOI: 10.6026/97320630008013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In silico studies on inhibitory effects of curcumin on multi drug resistance associated protein (MRP1) in retinoblastoma cells

Abstract: Multi Drug Resistance (MDR) is one of the major causes of chemotherapy failure in human malignancies. Curcumin, the active constituent of Curcuma longa is a proven anticancer agent potentially modulating the expression and function of these MDR proteins. In this study, we attempted to test curcumin for its potential to inhibit the expression and function of multidrug resistance associated protein 1 (MRP1) in retinoblastoma (RB) cell lines through western blot, RT-PCR and functional assays. In silico analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…[23] However, extensive studies on the bioavailability of curcumin have to be done to know its distribution in tissues after administration at pharmacological dose. Thus, curcumin may be used as a chemosensitizer in cancer therapy to reverse the MDR in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] However, extensive studies on the bioavailability of curcumin have to be done to know its distribution in tissues after administration at pharmacological dose. Thus, curcumin may be used as a chemosensitizer in cancer therapy to reverse the MDR in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…[21] Various modulators have been identified to reverse MDR mechanisms and thus sensitize MDR cancer cells to anti-cancer agents. [22] Our recent study found that curcumin is an inhibitors of MRP1[23] and LRP,[24] which have been found to play an important role in the development of drug resistance in tumor cells. It has been reported that curcumin is able to modulate the expression and function of P-gp in human gastric carcinoma cells and primary cultures of rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The MTT-bioassay data unambiguously showed that the pH-sensitive liposomal formulation of curcumin proved to significantly outclass the free drug in terms of The established high efficacy of formulated curcumin in resistant cells is of special interest, since this compound has been shown to restore the responsiveness to anticancer drugs and is considered as a potential multidrug-resistance reversal agent (Li et al, 2013;Li et al, 2011;Misra and Sahoo, 2011;Rao et al, 2014;Roy and Mukherjee, 2014;Sreekanth et al, 2011;Sreenivasan et al, 2012). The apoptosis assay firmly demonstrated that liposomal curcumin is a potent inducer of apoptotic DNA-fragmentation in HL-60, in compliance to preceding reports (Alaikov et al, 2007;Liao et al, 2008;Tan et al, 2006) and especially in HL-60/CDDP cells which proved to be more sensitive to the apoptogenic effects of equieffective levels of curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the simulated FC 60 +MRP-2 (=ABCC2) complex was characterized by the following parameters: the energy of interaction between the F小 60 and protein is -61.5 kJ/mol, the energy of steric clashes between the F小 60 and protein is 13.6 kJ/mol and, that importantly, in this case the binding pocket is completely filled ( Figure 2C The results of the molecular docking experiments suggest a direct interaction between FC 60 and three of the main proteins involved in multidrug resistance phenotypes of cancer cells -namely P-gp, MRP-1 and MRP-2. However, in a report devoted to analysis of interactions of MRP-1 with curcumin in silico, other aminoacid residues involved in formation of the protein binding cavity, were proposed [44]. The reason behind these differences may be the diverse modeling method used in this work and by Sreenivasan et al [44].…”
Section: Molecular Dockingmentioning
confidence: 93%